Translational control of tumor immune escape via the eIF4F–STAT1–PD-L1 axis in melanoma. (December 2018) - Cerezo, Michaël; Guemiri, Ramdane; Druillennec, Sabine; Girault, Isabelle; Malka-Mahieu, Hélène; Shen, Shensi; Allard, Delphine; Martineau, Sylvain; Welsch, Caroline; Agoussi, Sandrine; Estrada, Charlène; Adam, Julien; et al.
Abstract Preventing the immune escape of tumor cells by blocking inhibitory checkpoints, such as the interaction between programmed death ligand-1 (PD-L1) and programmed death-1 (PD-1) receptor, is a powerful anticancer approach. However, many patients do not respond to checkpoint blockade. Tumor PD-L1 expression is a potential efficacy biomarker, but the complex mechanisms underlying its regulation are not completely understood. Here, we show that the eukaryotic translation initiation complex, eIF4F, which binds the 5′ cap of mRNAs, regulates the surface expression of interferon-γ-induced PD-L1 on cancer cells by regulating translation of the mRNA encoding the signal transducer and activator of transcription 1 (STAT1) transcription factor. eIF4F complex formation correlates with response to immunotherapy in human melanoma. Pharmacological inhibition of eIF4A, the RNA helicase component of eIF4F, elicits powerful antitumor immune-mediated effects via PD-L1 downregulation. Thus, eIF4A inhibitors, in development as anticancer drugs, may also act as cancer immunotherapies. The translation initiation complex mediates tumor immune escape in melanoma by controllingSTAT1 mRNA levels and T lymphocyte–induced PD-L1 expression.